Innovative business strategies in the face of COVID-19: An approach to open innovation of SMEs in the Sonora Region of Mexico - Luis Enrique Valdez-Juárez; Mauricio Castillo-Vergara; Elva Alicia Ramos-Escobar (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The purpose of this study is to analyze and verify the effects of the business strategy (financial and market) and innovation management exerted on the economic indicators and business performances of SMEs in the south-central region of Sonora in Mexico. The effect of electronic commerce and the home office in the management of innovation and corporate performance is also analyzed. In addition, a multigroup analysis was carried out to check if there are significant differences between family and non-family businesses. The sample analyzed comprises 498 SMEs with between 6 and 250 employees in the commerce sector. To collect the information, a questionnaire was developed and applied to the online SME manager through the LimeSurvey Professional platform. The field work was carried out from February to October 2021. PLS-SEM was used for the data analysis. The results report that the business strategy (financial and market) does not have significant effects on the management of innovation and on the economic indicators of SMEs. On the other hand, innovation management has positive and significant effects on the economic indicators and business performance of SMEs. It is also revealed that economic indicators have a positive and significant effect on business performance. Open innovation strategies such as electronic commerce have positive and significant effects on innovation management and corporate performance. Similarly, the home office has significant effects on innovation management. Finally, unknown SMEs were found to be the best performers in innovation management and business performance. The study contributes to the development of the theory of competitive behavior and the theory of resources and capabilities.
Keywords: 650; business strategy; innovation management; open innovation; SMEs